PENGARUH CITRA MEREK, HARGA DAN PROMOSI DALAM KEPUTUSAN PEMBELIAN AIR MINUM DALAM KEMASAN (AMDK) RIVERO DI BANDAR LAMPUNG - Viola De Yusa; Anugrah Lihin Hastono (Universitas Muhammadiyah Metro Lampung, 2018)
Brand Image is the perception from consumer minds on a particular product. Price is marketing mix element which the function to the company profit. Promotion is the activity related to the correlation between the product and consumer target who buy the product. The purchase decision is the various consumer decision based on the particular assumptions i.e,, economic outlook, passive views, cognitive outlook, and emotional outlook. Rivero is one of the bottled water products purified by using the latest Reverse Osmosis (RO) filter technology. However, there are still a lot of consumers who do not know this product. The objective of this research was to determine the effect of the Rivero brand image, price and promotion on the Rivero consumers. The samples in this research was 97 respondents. The sampling technique used in this research was a purposive sampling. Data analysis technique used in this research was a multiple linier regression. Moreover, hypothesis tests conducted in this research were t test and f test. The result of this research showed that the Rivero brand image, price, and promotion affected the Rivero purchase decision.Keywords: Brand Image, Price, Promotion, Purchase Decision, Rivero